Combined Therapy of Ventricular Assist Device and Membrane Oxygenator for Profound Acute Cardiopulmonary Failure. Issue 6 (November 2017) - Fujita, Kevin; Takeda, Koji; Li, Boyangzi; Mauro, Christine; Kurlansky, Paul; Sreekanth, Sowmyashree; Han, Jiho; Truby, Lauren K.; Garan, A. Reshad; Topkara, Veli; Yuzefpolskaya, Melana; Colombo, Paolo; et al.
Abstract : Short-term ventricular assist devices (ST-VADs) have been effective in treating the patients with refractory cardiogenic shock. Membrane oxygenators (MOs) can be added to the circuit for concomitant, profound refractory hypoxia. This study reports the outcomes of combined therapy in this portion of patients. This is a retrospective review of 166 patients who received an ST-biventricular assist device (BiVAD) or right ventricular assist device (RVAD) for cardiogenic shock between November 2007 and November 2014. An MO was added to the RVAD for profound hypoxia refractory to maximized ventilation. Patients were divided into two groups: 33 with (MO-VAD [MV]) and 133 without (VAD only [VO]) an MO. Survival to discharge and adverse events were compared between groups. More MV than VO patients were intubated (93.9% vs . 59.4%; p < 0.001) and on veno-arterial extracorporeal membrane oxygenator (VA-ECMO) (72.7% vs. 19.5%; p < 0.001) before implantation. Survival to discharge (51.5% MV vs. 52.6% VO; p = 0.515) and 1 year survival (54.4% MV vs . 48.6% VO; p = 0.955) were not significantly different. MV patients had more prolonged intubation (69.7% vs . 37.6%; p < 0.001), tracheostomies (39.4% vs . 16.5%; p = 0.008), and a higher risk for bleeding ( p = 0.037). Patients suffering from cardiogenic shock with refractory hypoxia requiring combined ST-VAD and MO therapy appear to achieve similar mid-term survival despite increased risk for early complications.